Propeller Turbine Design for Power Generation - Marfizal; Sufiyanto; Dedi Wardianto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
The national electrification ratio is only 72.95%. As many as 27.05% of the territory in Indonesia has not been reached by electricity with various obstacles, one of which is because of the remote location so that access is difficult. One of the efforts to overcome the electricity problem is to take advantage of the potential energy sources around people's residences. One potential that might be used is a water energy source with low head and discharge. Ideally, this is done by using a generator system that uses a propeller type turbine. The difficulty of making propeller turbines is especially in the manufacture of housings and turbine blades. In this research, an attempt is made to simplify the turbine housing and turbine blades so that they are easy to manufacture. The design is made for Head (H) : 5 m Water flow (Q) : 0.11 m3/s Viscosity (ρ) : 998 kg/m3 Gravity (g) : 9.81 m/s2 Assumed hydraulic efficiency (ηh) : 0 ,80 Power (P) : 4,37 kW, Angle of attack (180o-β∞) 16o, Glide angle 55o, Thickness of inner blade(λ) 2,16o, Thickness of outer blade(δ) 2o. Simplification of the turbine housing is carried out by making the turbine housing from pipe iron and the simplification of the turbine blade is carried out by making turbine blades by eliminating the aerodynamic cross section of the blades, so that the blades can be made of steel plates without casting as is treated in aerodynamic sections. To see the effect of aerodynamic and non-aerodynamic cross-sectional shapes on efficiency, an efficiency test will be carried out.